Solution
We are given the following expression to evaluate:
[tex]\begin{gathered} f(x)=10x-10 \\ \\ \text{ Find:} \\ (f\mathrm{}f^{-1})(-10) \end{gathered}[/tex]- In order to solve this question, we should apply the following theorem:
[tex]f(f^{-1})(x)=x_{}[/tex]- Thus, in order to solve the question, we simply substitute x = -10. This is done below:
[tex]\begin{gathered} f(f^{-1})(x)=x \\ \text{put }x=-10 \\ \\ f(f^{-1})(-10)=-10\text{ (OPTION D)} \end{gathered}[/tex]Final Answer
The answer is:
[tex]f(f^{-1})(-10)=-10\text{ (OPTION D)}[/tex]